EFFECTS OF CYCLOPHOSPHAMIDE ON BLADDER AND RENAL FUNCTION IN PATIENTS WITH BREAST CANCER (Vietnam Journal of Community Medicine, 2022)
Objective: To investigate the effect of Cyclophosphomid on bladder and renal function in breastcancer patients.Subjects and methods: Descriptive-prospective cohort study, longitudinal follow-up on 68breast cancer patients at Thu Duc City Hospital who were treated with a regimen containingCyclophosphamide for 4-6 cycles.Results: Common clinical adverse effects of Cyclophosphamide on renal and bladder functionwere hypogastric pain (13.24%), hematuria (16.17%). Less common manifestations were urinaryfrequency (10.29%), painful urination (8.82%), cloudy urine (5.88%) and dysuria (4.41%). In theurine before and after treatment with Cyclophosphamide, there was a change in Microalbumin(from 5.24±0.64 to 16.21±2.01mg/dl). The results of cystoscopy showed that 19.05% of patientshad lesions. In which, 14.29% of bladder mucosal inflammation, 4.76% had ulceration and necrosis,there was not a bladder atrophy case. The rate of patients with bladder toxicity was 13.2%, the rateof patients without bladder toxicity was 86.8%.Conclusion: Common clinical side effects of Cyclophosphamide on renal and bladder functionwere hypogastric pain, hematuria. In the urine before and after treatment with Cyclophosphamidethere was a change in Microalbumin. Cystoscopy showed 14.29% of bladder mucosal inflammation,4.76% had ulceration and necrosis. The proportion of patients with bladder toxicity was 13.2%.
Keywords: Cyclophosphamide, bladder and renal function, breast cancer.